2010
DOI: 10.1510/icvts.2010.235515
|View full text |Cite
|
Sign up to set email alerts
|

Purulent spondylitis related to anastomotic fistula after esophageal cancer surgery

Abstract: A 73-year-old man underwent neoadjuvant chemotherapy followed by transhiatal esophagectomy with gastric tube reconstruction for advanced esophageal cancer with palliative intent. Cervical esophagogastrostomy with circular-stapled end-to-side anastomosis was performed; however, anastomotic fistula developed. Fever, severe pain in the nape of the neck and numbness of the left hand were noted after drainage by wide opening of cervicotomy and the administration of empiric antibiotics. Magnetic resonance imaging re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…To comprehensively analyze the risk factors of anastomotic leak, first of all, it is emphasized that a precise and scrupulous surgical technique plays a decisive role in the healing of anastomotic tissue. Precise surgical operation needs to ensure firm and stable tissue closure, good blood supply to the stomach or other organs replacing the esophagus and targeted treatment of anastomotic tension 3–7 . At present, gastric conduit, especially the thin conduit replacing the esophagus, has been accepted by more and more surgeons.…”
Section: Complex Clinical Presentations and Possible Causes Of Anasto...mentioning
confidence: 99%
“…To comprehensively analyze the risk factors of anastomotic leak, first of all, it is emphasized that a precise and scrupulous surgical technique plays a decisive role in the healing of anastomotic tissue. Precise surgical operation needs to ensure firm and stable tissue closure, good blood supply to the stomach or other organs replacing the esophagus and targeted treatment of anastomotic tension 3–7 . At present, gastric conduit, especially the thin conduit replacing the esophagus, has been accepted by more and more surgeons.…”
Section: Complex Clinical Presentations and Possible Causes Of Anasto...mentioning
confidence: 99%
“…Although there are several reports of PS following investigations or treatment for cancers, such as transoral surgery and chemoradiotherapy for head and neck cancers,24 25 surgical resection for oesophageal cancer26 and transrectal prostate biopsy for prostate cancer,27 this is the first report of PS following ESD for early gastric cancer. In conclusion, we experienced a rare case of PS following gastric ESD.…”
Section: Discussionmentioning
confidence: 90%
“…However, these postoperative sequelae after esophagectomy are extremely rare. Kakuta and Mecklenburg have reported an extremely rare case of esophagospinal fistula with cervical spondylodiscitis after esophagectomy with gastric tube [7,8]. These patients had received neoadjuvant chemotherapy or chemoradiotherapy for carcinoma of the thoracic esophagus, which is associated with immunosuppression.…”
Section: Discussionmentioning
confidence: 99%
“…These patients had received neoadjuvant chemotherapy or chemoradiotherapy for carcinoma of the thoracic esophagus, which is associated with immunosuppression. Kakuta et al [7] have reported that intraoperative injury in the prevertebral fascia is a causative factor. In 1995, Iannettoni et al [13] have reported that among 856 patients who underwent a cervical esophagogastric anastomosis after transhiatal esophagectomy, 3 (n = 1, vertebral body osteomyelitis; n = 2, epidural abscess with neurologic impairment) presented with cervical osteomyelitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation